The Empire Remains Shop - Connuck, Jesse (Columbia Books on Architecture and the City, 2018)
The Forest Does Not Employ Me Any More / Cooking Sections and Forager Collective – Buy the Rumor, Sell the News / Asunción Molinos – An Old World in a Former New World / Cooking Sections
Keywords: Installations (Art); Imperialism in art; Consumption (Economics) in art; Cooking Sections (Group); England